PEMANFAATAN LINGKUNGAN SEKOLAH SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA - Mudassir Nur (Jurnal Pendidikan Sang Surya, 2021)
This research is a classroom action research (Classroom Action Research), which generally aims to improve mathematics learning outcomes and attitudes towards mathematics of class IX2 students of SMP Negeri 32 Bulukumba. The research objectives: (1) describe the implementation of learning, (2) describe the mathematics learning outcomes achieved by class IX2 students, and (3) describe students' attitudes towards mathematics. This research was conducted at SMP Negeri 32 Bulukumba, Tanahlemo Village, Bontobahari District, Bulukumba Regency, South Sulawesi Province. The research subjects were students of class IX2 SMP Negeri 32 Bulukumba in the odd semester of the 2019 2020 academic year as many as 28 students. Subjects consisted of 17 female students and 11 male students. The research was carried out in 2 (two) cycles. Cycle I was carried out 6 times and 1 time was given a test of learning outcomes (daily test). Cycle II was carried out for 4 times of action and 1 time of giving learning outcomes tests (daily tests). The results showed that: (a) the average test results of learning outcomes (daily tests) of students in the first cycle was 60.00 increased to 63.00 in the second cycle, (b) students' attitudes towards mathematics increased in the form of cooperation, responsibility, honesty, confidence and care for the environment.